Diversity of true bugs (Insecta: Hemiptera: Heteroptera) from the El Impenetrable National Park, Argentina - Melo, María C; Castro-Huertas, Valentina; Minghetti, Eugenia; Olivera, Leonela; Serrano, Alejandro; Dellapé, Pablo M (Zootaxa, 2024)
The study of the Heteroptera (Hemiptera) fauna of the El Impenetrable National Park, resulted in an inventory composed of: Alydidae (2 spp.), Aradidae (1 sp.), Belostomatidae (5 spp.), Berytidae (1 sp.), Blissidae (1 sp.), Coreidae (11 spp.), Corixidae (2 spp.), Geocoridae (1 sp.), Gerridae (1 sp.), Hebridae (1 sp.), Largidae (4 spp.), Lygaeidae (5 spp.), Miridae (17 spp.), Nabidae (1 sp.), Notonectidae (1 sp.), Oxycarenidae (1 sp.), Pachygronthidae (1 sp.), Pachynomidae (2 spp.), Pentatomidae (16 spp.), Pleidae (1 sp.), Pyrrhocoridae (1 sp.), Reduviidae (30 spp.), Rhopalidae (5 spp.), Rhyparochromidae (12 spp.), Saldidae (1 sp.), Scutelleridae (2 spp.), Tingidae (1 sp.), and Veliidae (1 sp.). These findings include six new records for the Argentinean fauna: Prytanes foedus (Stål), Saldula pallipes (Fabricius), Camirus brevilinea (Walker), Atopozelus opsimus Elkins, Doldina bicarinata Stål, Rocconota sextuberculata Stål; and 39 new records for Chaco Province.